Deletion of the Gene rpoZ, Encoding the ω Subunit of RNA Polymerase, in Mycobacterium smegmatis Results in Fragmentation of the β′ Subunit in the Enzyme Assembly - Mathew, Renjith (American Society for Microbiology, 2005)
A deletion mutation in the gene rpoZ of Mycobacterium smegmatis causes reduced growth rate and a change in colony morphology. During purification of RNA polymerase from the mutant strain, the β′ subunit undergoes fragmentation but the fragments remain associated with the enzyme and maintain it in an active state until the whole destabilized assembly breaks down in the final step of purification. Complementation of the mutant strain with an integrated copy of the wild-type rpoZ brings back the wild-type colony morphology and improves the growth rate and activity of the enzyme, and the integrity of the β′ subunit remains unaffected.